Strategy for Strengthening Nation Character Building in Facing the Challenges of the Information Age - Pramono, Krido; Hanita, Margaretha (Journal of Strategic and Global Studies, 2021)
The development of technology makes human life easier and more aided, but behind that convenience there are challenges and threats to the fabric of society. Entering the information age or the era of the industrial revolution 4.0, there are many new problems that cover all aspects of human life, including national and state issues. The information age is pushing for insistence and struggle over the supremacy of information from one party to another. Perpetrators can be in the form of countries, multi-national companies, or non-state actors. For this reason, the idea of strengthening the nation's character as the glue and identity of a nation must be echoed again. Library research was used by the author in this article. This paper aims to uncover and predict threats, challenges, obstacles and disruptions that can emerge in the information age. The findings show the appreciation of the value of Pancasila also needs to be carried out with programs that are fluid and not too formalistic. It can implement with the help of interesting audiovisual media or through ideas that are close to the younger generation.